Analysis of Institutional Financial Management in Realizing Good Governance and Accountability of Financial Performance at Manado State University - Freddy S. Kawatu; Ramon Arthur Ferry Tumiwa; Merry Natalia Rumagit; Nova Mamuaya (Journal of International Conference Proceedings (JICP), 2018)
Long-term research objectives are new forms of innovation or models in financial management to realize good governance and accountability for financial performance at Manado State University. Demands for the management of public finance freely are the main problems that cannot be relied upon in clean government and good financial management (good governance) is an efficient, efficient and transparent financial capability. and accountable. In financial management the university work unit has been discussed in Law Number 17 of 2003 concerning State Finance and Government Regulation No. 39 of 2007 concerning Management of State Money. To find out how financial governance and financial performance accountability, can be used by using standard operating procedures, so that implementers can be used to facilitate, efficiently, transparently and accountably. This study aims to design a model or standard of financial procedures, as well as to measure the performance of financial management and accountability for financial performance at Manado State University. The plan of the research activity is to design a model or standard operating procedure in order to find out the results of institutional financial management and accountability of financial performance at Manado State University, so as to produce a product System or Operational Standards Procedures that can be directly carried out by the finance department executors. Keywords: Financial management, good corporate governance, accountability